Flourishing in head and neck cancer survivors. (11th March 2022) - Harris, Alexandria; Li, Jinhong; Atchison, Karley; Harrison, Christine; Hall, Daniel; VanderWeele, Tyler; Johnson, Jonas T.; Nilsen, Marci L.
Abstract: Background: There is a growing cohort of head and neck cancer (HNC) patients affected by late‐ and long‐term posttreatment side effects. Our study evaluates the relationship between the demographics, clinical characteristics, and posttreatment symptom burden with the subjective sense of flourishing among HNC survivors. Methods: A cross‐sectional, single‐center study of adult survivors of squamous cell cancer of the oral cavity, oropharynx, and larynx/hypopharynx who completed the Secure Flourishing Index (SFI) and patient‐reported outcomes related to depression, anxiety, swallowing dysfunction, neck disability, and insomnia between November 2020 and April 2021. Results: A total of 100, predominantly male (86%), survivors with an average age of 63.0 ± 9.6 were included in the study. Univariable analysis showed a significant association between higher flourishing scores and advanced age (95% CI: [0.011, 0.84], p  = 0.0441), normal diet (95% CI: [5.79, 31.18], p  = 0.0149), employment (95% CI: [1.24, 17.20], p  = 0.0239), higher income (95% CI: [7.30, 27.72], p  = 0.0248), and decreased reported difficulty paying for needs (95% CI: [−33.46, −18.88], p  < 0.001). Flourishing was inversely associated with higher symptoms of depression (95% CI: [−2.23, −1.15], p  < 0.001), anxiety (95% CI: [−1.92, ‐0.86], p  < 0.001), swallowing dysfunction (95% CI: [−0.77, −0.26], p  < 0.001), neck disability (95% CI: [−1.05, −0.35], p  < 0.001), and insomnia (95% CI: [−1.12, −0.22], p  = 0.004) in the multivariable analysis. Conclusions: Common late‐ and long‐term side effects of HNC treatment and financial hardship are associated with lower levels of flourishing or a more negative perception of life after treatment. Results highlight the importance of symptom burden for survivors' overall evaluation of their quality of life. Abstract : In this prospective, cross‐sectional study of 100 cancer survivors, symptoms of depression, anxiety, swallowing dysfunction, neck disability, insomnia along with perceived difficulty paying for needs was found to have a significant impact on human flourishing or the survivor's perception of well‐being. In head and neck cancer survivors, human flourishing is associated with a higher symptom burden and financial toxicity.